STUDENT PREFERENCES IN CORRECTIVE FEEDBACK: JORDANIAN EFL PERSPECTIVE - Al Dakheil, Raghad Mohammad Majed (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study investigated Jordanian EFL students' preferences regarding oral and written corrective feedback. The study sample consisted of (368) EFL students from the 8th, 9th, and 10th grades that were chosen conveniently from the public schools in Bani Obeid Directorate of Education. The study employed the descriptive analytical design using a questionnaire. The results of the study showed that Jordanian EFL students showed a moderate agreement regarding the effectiveness of oral and written corrective feedback. In the result for the students’ preferences regarding oral corrective feedback, EFL students reported that they prefer delayed grammatical corrective feedback. In contrast, in the result for the students’ preferences regarding written corrective feedback they reported that they prefer immediate corrective feedback that focuses on content errors. The results also showed that EFL students prefer explicit private corrective feedback over implicit public one. In light of the results, the study recommends that EFL teachers should take into consideration students’ needs and preferences when giving such feedback. In addition, oral and written corrective feedback should embedded in pre-service and in- service teacher training.